2011
DOI: 10.1002/hep.24385
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 receptor antagonists for liver transplant recipients: A systematic review and meta-analysis of controlled studies

Abstract: The use of IL-2Ra is associated with a lower incidence of acute rejection after transplantation. Concomitant immunosuppression can be reduced, avoiding long-term side effects of immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 35 publications
8
53
0
1
Order By: Relevance
“…This may be because CSA and RAP were administered in only a few cases, and only some patients switch immunosuppressants from FK506 to CSA or RAP. However, IL‐2Ra, a commonly used antibody, may have certain protective effects against NODAT onset . In the present study, IL‐2Ra administration reduced the risk of NODAT onset, with an OR of 0.427.…”
Section: Discussionsupporting
confidence: 45%
“…This may be because CSA and RAP were administered in only a few cases, and only some patients switch immunosuppressants from FK506 to CSA or RAP. However, IL‐2Ra, a commonly used antibody, may have certain protective effects against NODAT onset . In the present study, IL‐2Ra administration reduced the risk of NODAT onset, with an OR of 0.427.…”
Section: Discussionsupporting
confidence: 45%
“…A multicenter trial lately described that steroid‐free immunosuppression has no clear advantage over other regimens incorporating steroids , which was in accordance with our preceding studies . Most of our SLKT recipients received an interleukin‐2 receptor antagonist and/or lymphocyte‐depleting agent for induction, for which their use in HCV+ patients is yet to be determined . The influence of mycophenolate mofetil on recurrent HCV has also been the subject of conflicting results .…”
Section: Discussionsupporting
confidence: 79%
“…The rates of biopsy‐proven acute rejection and patient and graft survival were reportedly similar. These conclusions were supported by a recent meta‐analysis18; however, at least 1 study has reported no benefit to renal function from an anti–IL‐2RA induction regimen 19…”
Section: Practice Of Lt Immunosuppression In the United Statesmentioning
confidence: 85%